The Flypaper Effect in Intergovernmental Transfers and Local Expenditure - Ridho Daffa Wardana; Ananda, Candra Fajri (Journal of Development Economic and Social Studies, 2026)
This study analyzes the occurrence of the Flypaper Effect within regional financial management by utilizing variables such as Economic Growth, Local Revenue, Government Grant, and Budget Surplus in the Gerbangkertosusila Region over the period of 2010 to 2023. The findings derived from the Robust Common Effect model regression indicate that the variables PAD, DAU, DAK, DBH, and SiLPA exhibit a positive and statistically significant impact on Regional Expenditure, whereas Economic Growth demonstrates a negative influence that lacks statistical significance. It was observed that the coefficient values for all categories of Balance Funds exceeded those of PAD, thereby corroborating the hypothesis regarding the presence of the Flypaper Effect in the Gerbangkertosusila region throughout the research timeframe. Consequently, there is a necessity for strategies aimed at enhancing regional fiscal autonomy through the optimization of PAD and the fortification of local taxation authority.